A topical cell therapy approach for diabetic chronic ulcers: Effects of mesenchymal stromal cells associated with platelet-rich plasma - Stessuk, Talita; Ribeiro-Paes, João Tadeu [UNESP]; Colpas, Paula Tavares; Martins Alves, Paulo César; Rehder, Jussara; Bosnardo, Carla Aparecida Faccio; Guillaumon, Ana Terezinha; Forte, Andresa; Puzzi, Maria Beatriz (Wiley, 2020)
Background: Diabetic cutaneous ulcers are subjected to several physiological and biochemical defects, which contribute to wound chronicity and therapeutic failure. Platelet-rich plasma (PRP) has been used for stimulating tissue regeneration, and mesenchymal stromal cells (MSCs) have demonstrated therapeutic properties in all phases of skin regeneration in cell therapy studies. Aims: The objective of this study was to evaluate the therapeutic effects related to the use of a biomembrane composed of autologous MSCs and PRP on chronic wounds of diabetic patients (pre-post pilot study). Patients/Methods: Six diabetic patients with chronic wounds for more than 6 months were subjected to adipose tissue collection for isolation of MSCs, blood collection for PRP preparation, and topical administration of a biomembrane of MSCs and PRP on each chronic wound. The statistical difference regarding the evolution of ulcers was calculated by means of paired t test. Results: There was granulation tissue formation starting from 7 days after topical application. Total re-epithelialization occurred in 5 of the 9 lesions treated, and the mean wound healing rate (WHR) was 74.55% (±32.55%) after 90 days. No cicatricial hypertrophy or retraction was observed. Conclusion: Mesenchymal stromal cells topical therapy associated with PRP is well-tolerated and able to provide a reduction in ulcer area of diabetic chronic wounds.
Keywords: cell therapy; diabetes mellitus; mesenchymal stromal cells; platelet-rich plasma; wound healing